Highly Stable Carbon‐Free Ag/Co3O4‐Cathodes for Lithium‐Air Batteries: Electrochemical and Structural Investigations. Issue 19 (22nd July 2015) - Wittmaier, Dennis; Cañas, Natalia A.; Biswas, Indro; Friedrich, Kaspar Andreas
<x xml:space="preserve">Abstract</x> Lithium‐air batteries with an aqueous alkaline electrolyte promise a much higher practical energy density and capacity than conventional lithium‐ion batteries. However, high cathode overpotentials are some of the main problems during cycling. In our previous work, a catalyst combination of Ag and Co3O4 is found that reduces overpotential significantly, and is highly active and also long‐term stable. In the present investigations, X‐ray diffraction and X‐ray photoelectron spectroscopy are applied to study the structure and composition of the cathode material during oxygen reduction reaction and oxygen evolution reaction. Changes of the oxidation states during cycling are responsible for an enhanced oxygen evolution reaction current density but also for losses due to a lower electronic conductivity of the electrodes. The presence and formation of a mixed oxidation state for silver oxide (AgIAgIIIO2) at high potentials is identified. In contradiction to literature, time dependent X‐ray diffraction measurements evidence that this phase is not stable under dry conditions and progressively decays to Ag2O. Electrode mappings show a highly homogeneous oxidation of the electrodes during cycling and quantitative analysis of the observed phases is carried out by Rietveld analysis. Long‐term material behavior completes the investigations.